Enterprise in deprived areas: what role for start-ups?. (26th May 2009) - Devins, David
The promotion of enterprise in deprived areas is a key element of the UK government's policy to improve economic performance and social inclusion. This paper focuses on a key aspect of the agenda – the formation of new businesses (including self-employment) – and provides an overview of the development and implementation of New Labour policy before exploring the regional dimension and progress to date. The paper concludes with some implications for policy which question the rationale underpinning intervention, and draws attention to some issues which need to be considered if the policies are to meet the aspirations of government to the benefit of local communities.